Book Review: Arvind Krishna Mehrotra (Ed.), Arun Kolatkar. Collected Poems in English. (May 2016) - Joseph, Raphael
Arvind Krishna Mehrotra (Ed.), Arun Kolatkar. Collected Poems in English . Northumberland, UK: Bloodaxe, 2010, 383 pages, £12, ISBN 9-781852-248536